Tindak Tutur Ilokusi dalam Pementasan Drama “Teka Iku” Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Flores - Ri’a, Maria Polencys P.; Sareng, Anselmus Nong (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aims to find out how the results of the illocutionary speech acts in the play "Teka Iku" by Indonesian Language and Literature Education Students at the University of Flores. The problem in this research is what kinds of illusional speech acts are contained in the play "Teka Iku" Indonesian Language and Literature Education Student, University of Flores. The purpose of this study was to identify and describe the types of illocutions in the play Teka Iku by Indonesian Language and Literature Education Students at the University of Flores. This study uses a qualitative research type with a descriptive design. The data were collected using the speaking method, the listening method, and the recording method while the techniques used were observation, listening techniques, and note-taking and documentation techniques. The theory used in this research is pragmatic theory. The results of the analysis show that the use of the types of illocutionary speech acts of actors there are types of illocutionary acts consisting of types of affirmations, acts of asking, acts of suggesting, acts of doing, acts of authority of activities, and acts of placement